Fish functional trophic groups in headwater karst streams from the Upper Paraguay River basin - Severo-Neto, Francisco (2023)
Data obtained by direct observation of organisms in their natural habitats can provide valuable contributions regarding intra-and inter-specific interactions, as well as spatial distribution and trophic relationships. However, relatively few such data are available for the Neotropical ichthyofauna relative to the great species diversity of this region. We present data on the ichthyofauna in karst environments of the Serra da Bodoquena, Upper Paraguay River basin regarding their categorization into functional trophic groups. We used direct observations that focused on the most frequent feeding tactics and their spatial (vertical and horizontal) distribution in the channel. We observed 83 fish species in 17 functional trophic groups. The greatest species richness was concentrated in the Characidae and Loricariidae in the categories Diurnal Backwater Drift Feeders and Grazers, respectively. Regarding horizontal depth stratification, we found a positive relationship between the association of small fish with the shallow marginal habitats. This work represents a contribution to a region known for its high tourist potential and to the important diversity of the entire ichthyofauna of the Upper Paraguay basin region that requires proper conservation strategies for sustaining these species.